Natural and synthetic antimicrobials reduce adherence of enteroaggregative and enterohemorrhagic Escherichia coli to epithelial cells. - Yaraymi Ortiz; Alam García-Heredia; Angel Merino-Mascorro; Santos García; Luisa Solís-Soto; Norma Heredia (PLoS ONE)
Adherence of bacteria to the human intestinal mucosa can facilitate their internalization and the development of pathological processes. Escherichia coli O104:H4 is considered a hybrid strain (enteroaggregative hemorrhagic E. coli [EAHEC]), sharing virulence factors found in enterohemorrhagic (EHEC), and enteroaggregative (EAEC) E. coli pathotypes. The objective of this study was to analyze the effects of natural and synthetic antimicrobials (carvacrol, oregano extract, brazilin, palo de Brasil extract, and rifaximin) on the adherence of EHEC O157:H7, EAEC 042, and EAHEC O104:H4 to HEp-2 cells and to assess the expression of various genes involved in this process. Two concentrations of each antimicrobial that did not affect (p≤0.05) bacterial viability or damage the bacterial membrane integrity were used. Assays were conducted to determine whether the antimicrobials alter adhesion by affecting bacteria and/or alter adhesion by affecting the HEp-2 cells, whether the antimicrobials could detach bacteria previously adhered to HEp-2 cells, and whether the antimicrobials could modify the adherence ability exhibited by the bacteria for several cycles of adhesion assays. Giemsa stain and qPCR were used to assess the adhesion pattern and gene expression, respectively. The results showed that the antimicrobials affected the adherence abilities of the bacteria, with carvacrol, oregano extract, and rifaximin reducing up to 65% (p≤0.05) of E. coli adhered to HEp-2 cells. Carvacrol (10 mg/ml) was the most active compound against EHAEC O104:H4, even altering its aggregative adhesion pattern. There were changes in the expression of adhesion-related genes (aggR, pic, aap, aggA, and eae) in the bacteria and oxidative stress-related genes (SOD1, SOD2, CAT, and GPx) in the HEp-2 cells. In general, we demonstrated that carvacrol, oregano extract, and rifaximin at sub-minimal bactericidal concentrations interfere with target sites in E. coli, reducing the adhesion efficiency.